Multiple paths of green and low-carbon development in industrial parks: group analysis based on the TOE framework - Meng, Xin; Cheng, Yue; Xuan, Yuanhua (Frontiers in Environmental Science, 2024)
The green and low-carbon development of industrial parks plays an important role in promoting industrial and technological agglomeration,How to optimise their green and low-carbon development pathways is an important management question to be answered, requiring the examination of multiple path based on a histological perspective. Based on the TOE framework, this study selected 29 state-level economic and technological development zones (ETDZs) in China as research objects, and explored multiple sets of paths using fuzzy set qualitative comparison and necessity-contribution analysis. The study found that: (1) four promotion paths can be adopted for green low-carbon development of the zones: endogenous drive, balanced promotion, core support drive and comprehensive drive; (2) single environmental factor does not constitute a bottleneck hindering the green low-carbon development of the zones, which should be combined with the actual situation of the zones, and the balanced enhancement of the effectiveness of green and low-carbon should be realised through measures such as industrial policy, environmental risk prevention, and performance assessment of green policies. The results of the study deepen the rational understanding of the nature of the complex interaction of multiple factors behind the green and low-carbon development of industrial parks. In addition, the findings provide useful practical insights for green low-carbon construction.